Angelman syndrome with a chromosomal inversion 15 inv(p11q13) accompanied by a deletion in 15q11q13. Issue 12 (December 1992) - Webb, T; Clayton-Smith, J; Cheng, X J; Knoll, J H; Lalande, M; Pembrey, M E; Malcolm, S
Abstract : A family is described in which an inversion of chromosome 15, 15 inv(p11q13), is segregating. All family members are healthy except the proband who is a 10 year old boy with Angelman syndrome. Although the chromosomal inversion has been passed from the grandfather to both his son and his daughter with no ill effect, passage from daughter to grandson has resulted in a deletion of chromosome 15 material which is presumed to be the cause of Angelman syndrome in this boy. The probabilities of an inversion of this type being instrumental in causing the syndrome are discussed.